Amanda Rooms: capstone - Rooms, Amanda, artist (Colorado State University. Libraries, 2023)
The artist's statement: As a multimedia artist whose primary focus is sculpture and installation art, my goal is to let the materials guide my process in creating interactive artworks. My current body of work combines sculpting and painting, centered around my generation’s experience with unsolicited videos found through social media. These videos, which have content viewers don't consent to consuming, contribute to a lost sense of innocence. Unsolicited content is burned into the consumer's memory. There is no agency in viewing this unregulated media. The work I create focuses on conceptualizing how these videos affect us. The forms in this body of work aim to capture desensitization, curiosity, and discomfort these videos come with.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting